2020
DOI: 10.1371/journal.pone.0237007
|View full text |Cite
|
Sign up to set email alerts
|

Replicating and extending the effects of auditory religious cues on dishonest behavior

Abstract: Although scientists agree that replications are critical to the debate on the validity of religious priming research, religious priming replications are scarce. This paper attempts to replicate and extend previously observed effects of religious priming on ethical behavior. We test the effect of religious instrumental music on individuals' ethical behavior with university participants (N = 408) in the Czech Republic, Japan, and the US. Participants were randomly assigned to listen to one of three musical track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Second, shaping the context to increase self-referential thinking may also help increase honesty. For example, increasing the salience of the moral self by subconscious priming [82], listening to religious music [83], or observing (religious) rituals [84] appears to significantly reduce dishonesty. Moreover, increasing one's focus on the self through mindfulness may increase honesty as well [85].…”
Section: Discussionmentioning
confidence: 99%
“…Second, shaping the context to increase self-referential thinking may also help increase honesty. For example, increasing the salience of the moral self by subconscious priming [82], listening to religious music [83], or observing (religious) rituals [84] appears to significantly reduce dishonesty. Moreover, increasing one's focus on the self through mindfulness may increase honesty as well [85].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited from a student participant pool at Masaryk University, Czech Republic. Expectedly, sampling from this pool in our previous studies [ 46 , 47 ] revealed a young (mean age = 24) and secular sample where the modal answer on religiosity was ‘not religious’, and the modal answer on ritual participation was ‘never/not often’. Hence, testing our hypotheses on a population largely unengaged with costly religious signals should present a strong test of our hypothesis.…”
Section: Methodsmentioning
confidence: 99%
“…However, while these studies provide valuable support for CSTR by harnessing existing religious practices in various cultures, they usually cannot separate costly signals of commitment from other tangled factors and motivations underlying participation in these rituals such as personal vows to superhuman agents, anxiety management [42][43][44], or health improvement [27,45]. Nor can these studies disentangle the complex causal chains of religious systems that may affect cooperation [46,47]. Thus, it is not clear whether participation in religious practices is the primary driver of cooperative behaviour or whether it is the signalled cooperative phenotype driving the cooperative outputs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, whereas using the same priming materials across different field-sites confers multiple advantages (cf. Lang et al, 2016; Nichols et al, 2020), their strength and effectiveness might have been too low at sites that have never experienced a terrorist attack. Combining locally salient materials that would be comparable across sites should overcome these issues, although finding such materials would be extremely challenging.…”
Section: Discussionmentioning
confidence: 99%